Effect of thermo-mechanical treatment on microstructure and mechanical properties of wire-arc additively manufactured Al-Cu alloy - Zhang, Tao; Qin, Zhen-yang; Gong, Hai; Wu, Yun-xin; Chen, Xin (Springer, 2024)
Wire-arc additive manufacture (WAAM) has great potential for manufacturing of Al-Cu components. However, inferior mechanical properties of WAAM deposited material restrict its industrial application. Inter-layer cold rolling and thermo-mechanical heat treatment (T8) with pre-stretching deformation between solution and aging treatment were adopted in this study. Their effects on hardness, mechanical properties and microstructure were analyzed and compared to the conventional heat treatment (T6). The results show that cold rolling increases the hardness and strengths, which further increase with T8 treatment. The ultimate tensile strength (UTS) of 513 MPa and yield stress (YS) of 413 MPa can be obtained in the inter-layer cold-rolled sample with T8 treatment, which is much higher than that in the as-deposited samples. The cold-rolled samples show higher elongation than that of as-deposited ones due to significant elimination of porosity in cold rolling; while both the T6 and T8 treatments decrease the elongation. The cold rolling and pre-stretching deformation both contribute to the formation of dense and dispersive precipitated θ′ phases, which inhibits the dislocation movement and enhances the strengths; as a result, T8 treatment shows better strengthening effect than the T6 treatment. The strengthening mechanism was analyzed and it was mainly related to work hardening and precipitation strengthening.
Keywords: 4014 Manufacturing Engineering; 40 Engineering